The DINAMIKA KAMPANYE PILKADA 2024: STUDI KASUS IMPLEMENTASI KEBIJAKAN NOMOR 13 PKPU 13 TAHUN 2024 DI KOTA PALEMBANG - Gunawan, Indra; Alfitri (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This research is motivated by the low level of voter participation in Palembang City in the 2024 South Sumatra Governor and Deputy Governor Elections, which was recorded as the lowest in the province. The purpose of this research is to examine the implementation of the policy and analyze the factors that affect it in an effort to increase public participation in elections. This study uses George C. Edwards III's policy implementation theory, which emphasizes four important variables: communication, resources, executive disposition, and bureaucratic structure. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of PKPU No. 13 of 2024 in Palembang City has not been running optimally. One of the main factors inhibiting implementation is the weak human resources of the organizers, both in terms of competence and quantity. In addition, the lack of coordination between institutions also slows down the effectiveness of election campaigns. As a recommendation, this study suggests that the implementation of future regional elections can be carried out electronically (e-voting) to increase efficiency, transparency, and encourage voter participation more widely and easily accessible to the public.